Compendium of drawing techniques: 200 tips, and techniques and trade secrets - Krizek, Donna (Wellwood Quarto publishing plc, 2018)
"Just like having an art teacher on call 24 hours a day, this book is packed with hints and tips that will guide and inspire both beginners and more experienced artists alike. OVER 200 TECHNIQUES REVEALED: Both inspirational and practical, this book includes over 200 tips and step-by-step techniques organized to help you build on each skill you learn. With this book artists will learn how to use lines, contours, and shading to create subtle and dramatic effects, choose interesting subjects, design captivating compositions and more"--
Includes index.
Keywords: Drawing -- Technique; ART / Techniques / Drawing